Environmental Scanning and Communication Technology as a Gate for Sustainable Competitive advantage of Sanitary Ware (bathtub) Suppliers in Kingdom of Saudi Arabia. (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
Today globalization turned the world into a global village where event in one region transmits to others almost immediately. Communication technology has played big role and transformed many aspects of business; Internet is one of most important technology which has created e-commerce and a global digital economy with new opportunities. Social media such as websites Twitter, Facebook, LinkedIn and Pinterest have already demonstrated their potential for getting information also mobile technology have a lot of potential for gathering information. In spite of environmental turbulence, organizations must effectively depend on scanning environment and useful communication technology for operations and survival. It is crucial for every company to analyze strengths and weaknesses of the internal and external environment to enable the business sustain and growth. Both internal and external environmental scanning is important to be conducted but basically internal scanning will be done first as it will be the ground analysis to determine further direction of an organization. Increasing risk of error, failure to analyze environment included strength and weaknesses internally, opportunities and threats externally, and inefficient of communication technology may resulting to unsustainable the business in long term. Additionally a growing number of companies in Jeddah city led to the business competition between companies that increasingly tight and competitive. This paper sought the place of environmental scanning and role of communication technology as a way for providing information helpfully and as a means of business survival and sustainable competitive advantage. In this study we will focus on Suppliers who deal with sanitary ware (Bathtub) in Jeddah city, Kingdom of Saudi Arabia. Mostly people in Jeddah City prefer to purchase from various outlets vendors / retailers who are available usually in same area, according to their convenience, preference and selection. Increases in expectations and changing culinary style of consumers make the Sanitary Ware (Bathtub) business dynamic in general. Despite the increasing interest in the area there are very little researches on sustainable competitive advantage of sanitary ware vending service in our domestic market. Keeping these conditions in view, this study tries to explore the current scenario in which Sanitary Ware (Bathtub) has become a flourishing business for a lot of Suppliers as it has been successful in attracting a large mass of customers and projects.This study analyses environmental scanning and communication technology as a gate for sustainable competitive advantage of sanitary ware (Bathtub) in Jeddah city. The data analysis was based on 108 retailers who purchase bathtub sanitary ware from sanitary ware suppliers companies in Jeddah city, the data analysis was based on multivariate statistical techniques encompassing Factor analysis to test reliability, Percentage and frequency, descriptive analysis to describe the sample, multiple linear regressions via using SPSS analysis software. It identifies the most relevant understanding of environmental scanning and role of communication technology as agate for sustainable competitive advantage, and determines their influence in choosing of sanitary ware outlets. The results show that as environmental scanning and communication technologies (independent variables) have a positive influence on sustainable competitive advantage (dependent variable) of bathtub sanitary ware suppliers in Jeddah city.